PENYEGARAN KADER KESEHATAN JIWA UNTUK MENINGKATKAN KUNJUNGAN RUMAH DAN RUJUKAN PASIEN - sakdiah (Jurnal Pengabdian Pemersatu Bangsa, 2025)
Mental health is an essential component of overall health that still faces various challenges, including stigma, low literacy, and limited access to services. Mental health cadres play a strategic role in supporting community-based health services, particularly through home visits and patient referrals. However, limited knowledge and lack of continuous training remain obstacles in carrying out their duties. This activity aims to improve the capacity of mental health cadres through refresher training to enhance the quality of home visits and the effectiveness of patient referrals. The method used was a community service approach with an educational and participatory design through lectures, discussions, simulations, and mentoring, using a one group pretest-posttest design. The activity was conducted on March 23, 2025, in Gelumpang Baro District, Pidie Regency, involving 40 mental health cadres. The results showed a significant increase in cadres’ knowledge and skills after the intervention, as well as improved ability in conducting home visits and patient referrals. Therefore, refresher training for mental health cadres is effective in improving the quality of community-based mental health services.